A Microdevice in a Submicron CMOS for Closed-Loop Deep-Brain Stimulation (CLDBS) - Nordi, Tiago Matheus; Gounella, Rodrigo; Amorim, Marcio L. M.; Luppe, Maximiliam; Junior, João Navarro Soares; Afonso, Joao L.; Monteiro, Vitor; Afonso, Jose A.; Talamoni Fonoff, Erich; Colombari, Eduardo [UNESP]; Carmo, João Paulo (MDPI, 2024)
Deep-brain stimulation (DBS) is a highly effective and safe medical treatment that improves the lives of patients with a wide range of neurological and psychiatric diseases. It has been established as a first-line tool in the treatment of these conditions for the past two decades. Closed-loop deep-brain stimulation (CLDBS) advances this tool further by automatically adjusting the stimulation parameters in real time based on the brain’s response. In this context, this paper presents a low-noise amplifier (LNA) and a neurostimulator circuit fabricated using the low-power/low-voltage 65 nm CMOS process from TSMC. The circuits are specifically designed for implantable applications. To achieve the best tradeoff between input-referred noise and power consumption, metaheuristic algorithms were employed to determine and optimize the dimensions of the LNA devices during the design phase. Measurement results showed that the LNA had a gain of 41.2 dB; a 3 dB bandwidth spanning over three decades, from 1.5 Hz to 11.5 kHz; a power consumption of 5.9 µW; and an input-referred noise of 3.45 µVRMS, from 200 Hz to 11.5 kHz. The neurostimulator circuit is a programmable Howland current pump. Measurements have shown its capability to generate currents with arbitrary shapes and ranging from −325 µA to +318 µA. Simulations indicated a quiescent power consumption of 0.13 µW, with zero neurostimulation current. Both the LNA and the neurostimulator circuits are supplied with a 1.2 V voltage and occupy a microdevice area of 145 µm × 311 µm and 88 µm × 89 µm, respectively, making them suitable for implantation in applications involving closed-loop deep-brain stimulation.
Keywords: closed-loop deep-brain stimulation; implantable devices; low-noise amplifier; neurostimulation